Tailored treatment strategies: a new approach for modern management of atrial fibrillation. (16th March 2016) - Van Gelder, I. C.; Hobbelt, A. H.; Marcos, E. G.; Schotten, U.; Cappato, R.; Lewalter, T.; Schwieler, J.; Rienstra, M.; Boriani, G.
Abstract: Atrial fibrillation (AF) is not benign. Cardiovascular diseases and risk factors differ importantly amongst patients. Careful phenotyping with the aim to start tailored therapy may improve outcome and quality of life. Furthermore, structural remodelling plays an important role in initiation and progression of AF. Therapies that interfere in the remodelling processes are promising because they may modify the atrial substrate. However, success is still limited probably due to variations in the underlying substrate in individual patients. The most favourable effects of lifestyle changes on success of rhythm control have been demonstrated in obese patients with AF. Differences in genotype may also play an important role. Common gene variants have been associated with recurrence of AF after electrical cardioversion, antiarrhythmic drug therapy and catheter ablation. Therefore, both phenotyping and genotyping may become useful for patient selection in the future. Beside the choice of rate or rhythm control, and type of rhythm control, prevention of complications associated with AF may also differ depending on genotype and phenotype. Efficacy of stroke prevention has been well established, but bleeding remains a clinically relevant problem. Risk stratification is still cumbersome, especially in low‐risk patients and in those with a high bleeding risk. The decision whether to start anticoagulation (and if so which type of anticoagulant) or, alternatively, to implant an occlusion device of the left atrial appendage may also be improved by genotyping and phenotyping. In this review, we will summarize new insights into the roles of phenotype and genotype in generating more tailored treatment strategies in patients with AF and discuss several patient‐tailored treatment options. Abstract : Content List – Read more articles from the symposium: Atrial fibrillation ‐ from atrial extrasystoles to atrial cardiomyopathy. What have we learned from basic science and interventional procedures